Increased muscle sympathetic nerve activity and impaired baroreflex control in isolated REM-sleep behavior disorder. Issue 7 (July 2021) - Sayegh, Ana Luiza C.; Janzen, Annette; Strzedulla, Isabella; Birklein, Frank; Lautenschläger, Gothje; Oertel, Wolfgang H.; Krämer, Heidrun H.; Best, Christoph
Highlights: Muscle sympathetic activity is increased in isolated rapid eye movement (REM)-sleep behavior disorder (iRBD) patients. Baroreflex control is impaired in iRBD patients. Impaired inhibitory input of the locus coeruleus may disrupt the baroreflex circuit in iRBD patients. Abstract: Objective: Changes in baroreflex sensitivity have been reported in patients with idiopathic Parkinson's disease (PD). We sought to investigate the hypothesis that patients with isolated rapid eye movement (REM)-sleep behavior disorder (iRBD), known to be a prodromal stage for PD, will show abnormalities in baroreflex control. Methods: Ten iRBD patients were compared to 10 sex- and age-matched healthy controls. Their cardiovascular parameters and muscle sympathetic nerve activity (MSNA) were evaluated at rest and during baroreflex stimulation. Results: MSNA at rest was higher in iRBD patients (burst frequency [BF]: 44 ± 3 bursts/min; burst incidence [BI]: 60 ± 8 bursts/100 heartbeats) as compared to the controls (BF: 29 ± 3 bursts/min, p < 0.001; BI: 43 ± 9 bursts/100 heartbeats, p < 0.001). During baroreflex stimulation, iRBD patients showed increased absolute values of MSNA (BF: F = 62.728; p < 0.001; BI: F = 16.277; p < 0.001) as compared to the controls. The iRBD patients had decreased diastolic blood pressure at baseline and during lower body negative pressure, but the level of significance was not met. Conclusion: Our study shows increased MSNA and impaired baroreflex control in iRBD patients. We propose that the inhibitory effect of locus coeruleus on baroreflex function might be impaired, leading to the disinhibition of sympathetic outflow. Significance: These findings might reflect the destruction of brain areas due to the ascending P-α-synuclein deposits in iRBD patients.